Pengaturan Pembagian Harta Bersama Berdasarkan Putusan Mahkamah Konstitusi No. 69/PUU-XIII/2015 - Prabawa, I Gusti Ngurah Adi; Westra, I Ketut (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The purpose of this research is to study juridically regarding the division of joint assets both before and after the decision of the constitutional court no. 69/puu-xiii/2015. This paper uses normative legal research. The results of this study show that joint property arrangements before the Constitutional Court Decision No.69/PUU-XIII/2015 used the Marriage Law as a legal basis, where joint assets are regulated in article 35 paragraph (1) that assets acquired during marriage become joint property. Likewise with marriage agreements that must be made before the marriage takes place and or can be made in the form of an authentic deed in front of a notary, because there is no marriage agreement made before the marriage is carried out, then all the assets of the husband and wife, the mixing of this marriage agreement has been determined in the regulations laws and regulations as long as they do not violate the social order and general order prevailing in society. Implementation of the division of joint assets after the Constitutional Court Decision No. 69/PUU-XIII/2015 during the marriage period and after the divorce, where before or in progress of the marriage, may also be made after the marriage is carried out or while in a marital relationship it is permissible to make a marriage agreement. So when in the future there is a legal event in the form of divorce, there will be a separation of joint assets. Tujuan penelitian ini mengkaji pengaturan pembagian harta bersama baik itu sebelum dan pasca putusan mahkamah konstitusi no. 69/puu-xiii/2015. Tulisan ini mempergunakan peneitian hukum normatif. Hasil penelitian ini menunjukan pengaturan harta bersama sebelum adanya Putusan Mahkamah Konstitusi No.69/PUU-XIII/2015 menggunakan UU Perkawinan sebagai landasan hukum, dimana harta bersama diatur pada pasal 35 ayat (1) bahwa Harta benda yang diperoleh selama perkawinan menjadi harta Bersama. Begitu juga dengan perjanjian perkawinan yang harus dilakukan sebelum perkawinan dilangsungkan dan atau dapat dibuat dalam bentuk akta otentik dimuka notaris, oleh sebab tidak ada perjanjian perkawinan yang dibuat sebelum perkawinan dilakukan maka semua harta suami dan isteri tersebut maka terjadinya perbauran perjanjian perkawinan ini telah ditentukan dalam peraturan perundang–undangan sepanjang tidak menyalahi tata susila dan ketentraman umum yang berlaku dalam masyarakat. Pelaksanaan pembagian harta bersama pasca adanya Putusan Mahkamah Konstitusi No.69/PUU-XIII/2015 selama masa perkawinan dan setelah perceraian, dimana sebelum atau sedang berlangsungnya perkawinan, boleh juga dibuat pasca perkawinan dilakukan atau selama dalam hubungan perkawinan diperbolehkan membuat perjanjian perkawinan. Sehinngga Ketika dikemudian hari terjadi peristiwa hukum berupa perceraian maka terjadi pemisahan harta Bersama.